A Comprehensive Review of Possible Resistant Starch in Getuk: Its Formation, Health Effects, and Potential Applications as Prebiotics - Muhammad Iqbal Fanani Gunawan (Agroindustrial Journal, 2023)
This review aims to give a thorough understanding of how resistant starch is produced, how it affects health, and how it probably contains in traditional Indonesian snack called getuk. Resistant starch, a type of starch that resists digestion in the small intestine, has drawn a lot of attention. In order to learn more about resistant starch formation in getuk, this review includes a thorough study of the relevant databases, research articles, and scientific literature that is currently available. It explains the effects of various processing techniques, including cooking and cooling on the possible formation of resistant starch in the snack. The potential health implications of resistant starch consumption in getuk are also examined in this review. It has been discovered that resistant starch provides a number of advantages, such as improved glycemic management, prolonged satiety, gut microbiota modulation, increased mineral absorption, and a decreased risk of obesity, type 2 diabetes, and colorectal cancer. The primary cause of these effects is attributed to the fermentation of resistant starch by colonic bacteria, which results in the production of short-chain fatty acids and other bioactive substances. The review looks at Getuk’s potential uses as a resistant starch carrier in the creation of functional foods. The snack is a perfect candidate for adding extra bioactive substances such as fiber, and prebiotics to improve its nutritional profile and functional qualities because of its distinctive texture, flavor, and cultural importance. Overall, this review emphasizes the production of resistant starch during processing of getuk and indicates the potential health advantages of its ingestion. It offers insightful information about the importance of this traditional Indonesian snack as a carrier of resistant starch and its prospective uses in the creation of functional meals. To fully utilize getuk as a source of resistant starch in the production of functional foods, additional study is required to optimize processing methods, assess consumer acceptability, and explore novel formulations.